Do Ethnic-Racial Identity Dimensions Moderate the Relations of Outgroup Discrimination and Ingroup Marginalization to Self-esteem in Black and Latinx Undergraduates? - Wilson, Antoinette R. (Race and social problems, 2023)
Guided by social identity and intergroup theory, we tested how two facets of ethnic-racial identity—felt typicality (perceived similarity to other ingroup members) and ingroup ties (felt closeness to other ingroup members)—potentially buffer the negative effects of outgroup discrimination and ingroup marginalization on self-esteem. Participants included 407 Latinx (65%) and Black (35%) undergraduates (Mage = 24.72 years, 79% women, 21% men) who completed an online survey. Our analyses yielded three key findings. First, both outgroup discrimination and ingroup marginalization predicted lower self-esteem; however, this association was significantly stronger with ingroup marginalization than outgroup discrimination. Second, the association between ingroup marginalization and self-esteem was reduced when ethnic-racial identity variables were controlled. Felt ethnic-racial typicality additionally moderated the association between ingroup marginalization and self-esteem—whereby the negative association was stronger when individuals felt higher ethnic-racial typicality. Our findings expand understanding of the impact of marginalization and discrimination from those within and outside of one’s ethnic-racial group, respectively. We also discuss the differing roles of ethnic-racial identity when experiencing outgroup discrimination and ingroup marginalization.